The Crisis of Authority in Global Culture: An Interdisciplinary Analysis of Contemporary Shifts in Epistemology, Values, and Truth - John Massie; Yohanes Nduru; Herbin Simanjuntak (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The crisis of authority in global culture is a complex phenomenon reflecting a fundamental shift in how humans understand truth, values, and the sources of legitimacy of knowledge. This research focuses on the dynamics of epistemological change in global society influenced by digital technology, cultural relativism, and value pluralism. The main issue studied is how this crisis of authority influences the construction of truth and value systems in contemporary society, as well as its implications for social and spiritual life. The aim of this research is to develop an interdisciplinary analysis that integrates perspectives from philosophy, sociology, theology, and media studies in understanding this phenomenon. The method used is a qualitative approach based on systematic literature studies with a critical analysis of recent academic sources. The main findings indicate that the crisis of authority is characterized not only by the weakening of traditional institutions but also by the emergence of